Strategi Pendidikan Entrepreneurship di Pesantren Al-Mawaddah Kudus - Afandi, Zaenal (Universitas Islam Negeri Sunan Kudus, 2019)
Generally Boarding School take religious and morals material as the most priority, but ignoring skills. The consequences is Boarding School graduates always feeling awkward when back to their hometown. Facing that condition, entrepreneurship education become one of concrete solution. This research describe about entrepreneurship education strategy in Al-Mawaddah Boarding School Centre Honggosoco Jekulo Kudus. This reseach belong to field research. Researcher collect data using interview method, observation and documentation. While for the analysts researcher using qualitative descriptive analyst thechniques. This research is held in Al-Mawaddah Boarding School Centre Honggosoco Jekulo Kudus. The result of this research showing that 1). The implementation of entrepreneurship education runs effectively. It can be seen from material that have been submitted and enthusiasm of the santri in running the entrepreneur owned by the Boarding School. 2) is the development strategy of entrepreneurship education in Al Mawaddah Boarding School quite successful that proved by the growing entrepreneurship of Boarding School.